Load, pressure, rubble pile geometry and video data from model-scale tests on shallow water ice-structure interaction - Ida Lemström; Arttu Polojärvi; Otto Puolakka; Jukka Tuhkuri (Data in Brief, 2022)
This paper presents the data from model-scale experiments on shallow water ice-structure interaction. The data is related to the original research article ‘Model-scale tests on ice-structure interaction in shallow water: Global ice loads and the ice loading process’ Lemström et al.(2022)[1]. During the conducted experiments, a ten-meter wide initially intact ice sheet was pushed against a sloping structure of the same width. As the ice failed against the structure, a grounded rubble pile accumulated in front of it. The structure consisted of ten identical one-meter-wide segments and the horizontal load on each of these segments was measured independently with load cells. These measurements are presented as load-time datasets. The horizontal load acting on the false bottom was measured with load cells and are also presented as load-time datasets. Furthermore, the ice pressure on two of the segments was measured with tactile sensors. These pressure measurements are presented as array-based pressure-time datasets. Video footage filmed from two different video angles is published. In addition, the coordinates of the rubble pile geometries at the end of each experiment are published. The data includes the top and side rubble pile geometries. In total, seven experiments were conducted. The data can be used by researchers, engineers and designers who work with ice structure interaction related issues in order to, for instance, optimize the design of offshore structures, improve ice load predictions or develop future experiments and simulations.